First performance test of the iron-based superconducting racetrack coils at 10 T. (2nd February 2021) - Zhang, Zhan; Wang, Dongliang; Wei, Shaoqing; Wang, Yingzhe; Wang, Chengtao; Zhang, Zhen; Yao, Huanli; Zhang, Xianping; Liu, Fang; Liu, Huajun; Ma, Yanwei; Xu, Qingjin; et al.
Abstract: Iron-based superconducting (IBS) racetrack coils were firstly fabricated by using 100-m 7-filamentary Ba1-x Kx Fe2 As2 (Ba122) tapes at the Institute of High Energy Physics, Chinese Academy of Sciences (IHEP, CAS). The IBS tape was wound in parallel with stainless steel tape to withstand the high tensile hoop stress under high magnetic field. After the heat treatment, the coils were impregnated with epoxy resin. Then the IBS coils were tested in a low-temperature superconducting Common-Coil dipole magnet which provided a maximum background field of 10 T at 4.2 K. Most importantly, the best IBS racetrack coil quenched at 4.2 K and 10 T with an operating current of 65 A, which is still as high as 86.7% of critical current of the short sample at 10 T. The details of the fabrication process and performance test results were presented in this paper. The performance test demonstrated the IBS conductor is a promising candidate for the application of high field magnets especially for future high-energy accelerators.